Single-Cell RNA-Seq of Bone Marrow Cells in Aplastic Anemia - Tonglin, Hu; Yanna, Zhao; Xiaoling, Yu; Ruilan, Gao; Liming, Yin (Frontiers in Genetics, 2022)
Aplastic anemia (AA) is an autoimmune disease characterized by peripheral blood pancytopenia and bone marrow failure. Recently, researcher study verifies bone marrow failure of AA patients result from hematopoietic stem and progenitor cells (HSPC) attack by active T cells. Nonetheless, B cells as one of the important immune cell, whether destructing the hematopoiesis is still unclear. Here, we performed a large-scale single-cell transcriptomic sequencing of 20,000 bone marrow cells from AA patients and healthy donors. We identified 17 clusters and differentially expressed genes in each clusters relative to other clusters, which were considered potential marker genes in each clusters. The top differentially expressed genes in HSPCs (S100A8, RETN and TNFAIP3), monocytes (CXCL8, JUN and IL1B) and neutrophils and granulocytes (CXCL8, NFKBIA and MT-CYB) were related to immune and inflammatory injury. Then, we analyzed the B cell receptor (BCR) diversities and pairing frequencies of V and J genes. The highest pairing frequencies in AA patients were IGHV3-20-IGKJ2, IGHV3-20-IGKJ4 and IGHV3-20-IGHLJ2. Meanwhile, there were three V genes, including IGHV3-7, IGHV3-33 and IGLV2-11, with elevated expression in B cells from AA patients. We further identified cell type-specific ligand-receptor in B cell interaction with hematopoietic cell in bone marrow. The changed ligand-receptor pairs involved antigen presentation, inflammation, apoptosis and proliferation of B cell. These data showed the transcriptomic landscape of hematopoiesis in AA at single-cell resolution, providing new insights into hematopoiesis failure related with aberrant of B cells and provide available target of treatment for AA.